Capillary microarchitectural changes in Cushing's syndrome - ILGIN, CAN; YAVUZ, DİLEK; APAYDIN, TUĞÇE (Academic Press Inc., 2022)
Purpose: Macrovascular alterations are prominent in Cushing's syndrome (CS). Microvascular abnormalities are yet to be established. This cross-sectional observational study aimed to evaluate microvascular changes in nailfold capillaries and their association with disease status and carotid intima-media thickness (CIMT) as a marker of atherosclerosis. Methods: A total of 70 patients with CS [46 (65.7%) ACTH-dependent pituitary adenoma and 24 (34.3%) adrenocortical adenomas] and 100 healthy controls were enrolled. The microvascular structure was evaluated using nailfold video-capillaroscopy (NVC). Results: The median number of capillaries was less [10 mm (IQR: 2, min-max:7–14) vs. 11 mm (IQR: 2, min-max:9–19) (p < 0.001)], the median limb diameter and capillary width were wider in the CS group than in the controls (p = 0.016 and p = 0.002, respectively). Microhemorrhages within limited areas were more frequent in the CS group than in the controls (p = 0.046). Observed capillary changes were similar among the patients with CS with remission or active disease. CIMT levels were higher in the CS group than in the controls and similar in subjects with active disease and remission. Univariate logistic regression analyses revealed that the number of capillaries and capillary widths were associated with body mass index (BMI), the presence of type 2 diabetes mellitus, HbA1c, and CIMT. Conclusion: Morphologic alterations present similarly in nailfold capillaries in subjects with CS regardless of disease status, resembling changes in chronic atherosclerotic diseases. Microvascular changes in nailfold capillaries measured using NVC can be used as a marker in the assessment of cardiovascular risk in patients with CS. © 2022 Elsevier Inc.
Keywords: Cushing's disease; Cushing's syndrome, capillaroscopy, microcirculation; Microangiopathy